An abrupt change in the African monsoon at the end of the Younger Dryas - (:unkn) unknown (My University, 2007)
High-resolution studies of variations in the elemental and stable carbon- and nitrogen-isotope composition of organic matter in cores from Lakes Malawi, Tanganyika, and Bosumtwi (tropical Africa) indicate an abrupt change in the wind-driven circulation of these lakes that, within the limits of available chronologies, was contemporaneous with the end of the Younger Dryas in the northern hemisphere. The change was also coincident with shifts in surface winds recorded in cores from off the west and northeast coasts of Africa. A range of other proxies indicate that these changes in wind regime were accompanied by a marked increase in precipitation in the northern tropics. Africa south of ~5°-10°S, on the other hand, initially suffered drought conditions. Together, the evidence suggests an abrupt northward translation of the African monsoon system at circa 11.5 ± 0.25 ka B.P. The data assembled here contribute to a growing body of work showing that the Younger Dryas was a major climatic excursion in tropical Africa. Furthermore, they add substance to recent suggestions that climatic events in the southern hemisphere may have played a significant role in the abrupt demise of the Younger Dryas
Keywords: African Research